Lung xenotransplantation. Issue 6 (December 2017) - Sahara, Hisashi; Watanabe, Hironosuke; Pomposelli, Thomas; Yamada, Kazuhiko
Abstract : Purpose of review: This review describes the most recent progress in xeno lung transplantation (XLTx) to date. It describes the potential mechanisms of early xeno lung graft loss, as well as the latest therapeutic strategies to overcome them. Recent findings: Using ex-vivo perfusion models of porcine lungs with human blood, the use of genetically modified pig lungs along with novel pharmaceutical approaches has recently been studied. Strategies that have demonstrated improved lung survival include the knockout of known xenoantigens (GalTKO and N-glycolylneuraminic acid-KO), genes that regulate complement activation (hCD46 and hCD55), as well as the inflammation/coagulation cascade (human leukocyte antigen-E, human thrombomodulin, human endothelial protein C receptor, hCD47, hCD39, hCD73 and heme oxygenase-1). Furthermore, pharmacologic interventions including the depletion of pulmonary intravascular macrophages or von Willebrand factor, inhibition of thromboxane synthase and blockade of histamine receptors have also demonstrated protective effects on xeno lung grafts. Using in-vivo pig to nonhuman primate lung transplant models, these approaches have been shown to extend pulmonary xenograft survival to 5 days. Summary: The development of new multitransgenic GalTKO pigs has demonstrated prolongation of porcine xenograft survival; however, advancement in XLTx has remained frustratingly limited. Further intensive and innovative strategies including genetic manipulation of donors, as well as inflammation/coagulation dysregulation, are required to make XLTx a clinical possibility.